Crescimento e tolerância de Senna multijuga e Erythrina crista-galli com a utilização de turfa em solo contaminado com zinco - Scheid, Douglas Leandro (2016)
The amount of areas contaminated with heavy metals is constantly increasing. Zinc is a micronutrient and also a contaminant when found in larger quantities. Contaminated areas require recovery, and one of the techniques is the use of plant species, but studies are needed to identify suitable species. The objective of this study was to evaluate the initial development and tolerance Senna multijuga and Erythrina crista-galli the soil contaminated with zinc and use of peat. Thus it was conducted three experiments. The first studied the growth, tolerance and copper accumulation in seedlings of Senna multijuga and Erythrina crista-galli. In the second study evaluated the effect of peat (200 ml of peat kg-1 in soil) and the growth and tolerance Senna multijuga in soil contaminated with zinc. In the third, we evaluated the use of Erythrina crista-galli L. and peat zinc contaminated soil phytoremediation. In the first study, E. crista-galli and S. multijuga decreased in morphological parameters with increasing doses, while the zinc concentration in the aerial part and root increased with doses in both species. Both species have low translocation of zinc and were sensitive soil contamination with zinc. The species is capable of phytostabilization of zinc. With the use of peat, zinc levels in the shoot and roots are smaller and soil contaminated with zinc tolerance of Senna multijuga seedlings is higher. In Erythrina crista-galli translocation of Zn is greater with the use of the peat, but still shows moderate tolerance to Zn. The use of peat does not allow the species to be considered phytoextractor of Zn.